Kajian Kinerja Sistem Polder sebagai Model Pengembangan Drainase Kota Semarang Bagian Bawah dengan Balanced Scorecard - Nugroho, Hari; Kurniani, Dwi; Asiska, Mega; Nuraini, Nuraini (Department of Civil Engineering, Diponegoro University, 2016)
One of the technological flood control and rob in the big cities is the polder system that include drainage systems , retention ponds, levees that surround the area, as well as the pump and / floodgates, as the area of integrated water management system. Likewise, as the coastal city of Semarang in Indonesia has built some of the polder which has been in operation or under construction. To assess the success of the polder management, necessary for a study to determine the performance of the system in controlling the flood in Semarang. Assessment of performance of the system as a whole polder in this study used the concept of the Balanced Scorecard (BSC). The results of this study demonstrate the performance of the polder in Semarang is an ideal: Polder Tanah Mas (73.81 / 100), then Polder Banger (67.21 / 100), Polder Kali Semarang (58.70/100) and the Polder Tawang (58.65/100). The performance of the Polder system above can not be separated from the existence of an independent governing body and had been prepared much earlier. So the presence of the governing body needs to be prepared in the polder system development. To improve performance, the polder-existing polder in Semarang needs to be improved its performance by improving the performance indicators is still less based on this research primarily on indicators: financial, management agencies and learning and development.